Factors Affecting Under-Five Mortality Rate (U5MR) in India- National Family Health Survey (NFHS) 5 Factsheet What It Speaks? - Nikita Gaur; Tanya Singh; Aanchal Singhal; Abhimanyu Dabas; Sudhanshu Batra; Sidharth Mishra (Medsci Publications, 2023)
Introduction: In developing countries various factors lead to Under-5 Mortality and irreversible losses which can be prevented by proper measures take on factors affecting to it. Objective: This study was conducted to analyse the changing trends of Under-5 Mortality in India. The new National Family Health Survey (5th round) which was published recently came up with several new findings, which were both encouraging and disheartening and also one of the major Sustainable Development Goals. Method: A secondary data analysis was conducted of NFHS factsheets to study the U5MR in India. The indicators which had a correlation either positive or negative with the Under-five mortality rate were included. Result- When we look at the result, few states' performance is encouraging because they have shown some of the best declines. Correlation was found between dependant variable that is U5MR which is a dependent variable and several independent variables which concluded that factors like Women literacy, Men literacy, Breastfeeding, Nutritional insufficiencies, Caesarean delivery, ANC visits and IFA consumptions are negatively associated with U5MR. Conclusion: Various steps have been taken in order to improve our healthcare sector since independence, every government had their fair share of contribution, that's the reason why we are this stage. Now it's time to increase efforts with targeted interventions to solve this problem and complete our commitment towards the SDGs.